James J. Dinsmore letter to Thomas H. Kent regarding bird sightings, May 27, 1980 - Dinsmore, James J.et al (1980)
Field notes contributed by James J. Dinsmore in a letter to Thomas H. Kent, May 27, 1980 with observers John C. Robinson, David A. Newhouse, Hank and Linda Zaletel and students. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed